2019
DOI: 10.7554/elife.49424
|View full text |Cite
|
Sign up to set email alerts
|

Single-cell transcriptomes and whole-brain projections of serotonin neurons in the mouse dorsal and median raphe nuclei

Abstract: Serotonin neurons of the dorsal and median raphe nuclei (DR, MR) collectively innervate the entire forebrain and midbrain, modulating diverse physiology and behavior. To gain a fundamental understanding of their molecular heterogeneity, we used plate-based single-cell RNA-sequencing to generate a comprehensive dataset comprising eleven transcriptomically distinct serotonin neuron clusters. Systematic in situ hybridization mapped specific clusters to the principal DR, caudal DR, or MR. These transcriptomic clus… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
225
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 239 publications
(236 citation statements)
references
References 92 publications
11
225
0
Order By: Relevance
“…We observed that stimulation of NPVF neurons results in increased GCaMP6s fluorescence in most serotonergic IRa neurons, although a significant minority of IRa neurons show reduced GCaMP6s fluorescence. These observations suggest that there are at least two functionally distinct neuronal populations among tph2 -expressing IRa neurons, consistent with studies of the mammalian RN that identified molecularly distinct sub-populations with distinct efferent projection patterns and functions (Huang et al, 2019; Ren et al, 2018; Ren et al, 2019). The NPVF neuron-induced inhibition of a sub-population of IRa neurons that we observed is consistent with a previous study which reported that optogenetic stimulation of NPVF neurons resulted in decreased GCaMP6s fluorescence in IRa neurons (Madelaine et al, 2017), although the effect was small and slow compared to our data.…”
Section: Discussionsupporting
confidence: 87%
“…We observed that stimulation of NPVF neurons results in increased GCaMP6s fluorescence in most serotonergic IRa neurons, although a significant minority of IRa neurons show reduced GCaMP6s fluorescence. These observations suggest that there are at least two functionally distinct neuronal populations among tph2 -expressing IRa neurons, consistent with studies of the mammalian RN that identified molecularly distinct sub-populations with distinct efferent projection patterns and functions (Huang et al, 2019; Ren et al, 2018; Ren et al, 2019). The NPVF neuron-induced inhibition of a sub-population of IRa neurons that we observed is consistent with a previous study which reported that optogenetic stimulation of NPVF neurons resulted in decreased GCaMP6s fluorescence in IRa neurons (Madelaine et al, 2017), although the effect was small and slow compared to our data.…”
Section: Discussionsupporting
confidence: 87%
“…Interestingly, simultaneous recording 5-HT1.0 in OFC and BNST revealed tight correlation in fluorescence during NREM sleep (Fig. 3h,i), suggesting global synchrony of the 5-HT signaling despite of the region-specific innervation by different subpopulations of the serotonergic neurons in DRN 23, 24 . Lastly, consistent with our previous findings, we found that treating mice with the 5-HT receptor antagonist Met largely blocked the fluorescence change of the 5-HT1.0 sensor (Fig.…”
Section: Mainmentioning
confidence: 90%
“…Single serotonergic neurons can span sensory networks within the same modality and therefore have the potential to modulate different processing stages simultaneously. Recent work mapping the projection patterns of 50 serotonergic Raphe neurons demonstrated that similarly to the CSDn, a single neuron can target several olfactory areas including the main olfactory bulb, accessory olfactory bulb, and piriform cortex [19]. The degree to which the influence of a single serotonergic neuron is conserved across processing stages is unknown, however work in mice suggests that the functional roles of serotonergic neurons can differ between networks.…”
Section: Discussionmentioning
confidence: 99%